2010
DOI: 10.1158/1055-9965.disp-10-b20
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B20: Community bridges to cancer clinical trials: Evaluating community education modules

Abstract: Cancer clinical trials are a source for high-quality cancer care. However, they are often perceived as an option of last resort. Raising consciousness about cancer clinical trials in community settings may lead to informed decision-making about cancer clinical trials. Objective: To modify and pilot training materials for a community organization intervention to positively impact knowledge, attitudes, beliefs, and behaviors regarding cancer research in African American communities in North Caroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…On a larger, community level, given the willingness to participate in non-treatment trials and the altruism shown by participants in the current study, perhaps non-treatment trials can be used to establish familiarity with clinical trials in general and increase acceptability of treatment trials within the community. Ongoing studies such as the NCI-funded pilot study Community Bridges to Cancer Clinical Trials , will help further inform the cancer research community regarding these and related issues of community knowledge and favorable attitudes towards clinical trials [47]. …”
Section: Discussionmentioning
confidence: 99%
“…On a larger, community level, given the willingness to participate in non-treatment trials and the altruism shown by participants in the current study, perhaps non-treatment trials can be used to establish familiarity with clinical trials in general and increase acceptability of treatment trials within the community. Ongoing studies such as the NCI-funded pilot study Community Bridges to Cancer Clinical Trials , will help further inform the cancer research community regarding these and related issues of community knowledge and favorable attitudes towards clinical trials [47]. …”
Section: Discussionmentioning
confidence: 99%
“…The curriculum was influenced by previous training developed by the instructors. Examples include the Meharry-Vanderbilt Community Engaged Research Core “Art of Recruitment” module which was originally created in 2014 and subsequently adapted and tailored for specific trials [ 29 ], the curricula developed by the Education Network to Advance Cancer Clinical Trials (ENACCT) to train cancer clinical trial research staff on improving recruitment and retention practices, especially for minority groups [ 24 , 30 ], and train-the-trainer programs with community leaders to increase cancer clinical trial participation among minority groups [ 30 35 ].…”
Section: Methodsmentioning
confidence: 99%